Early events after infection of Escherichia coli by bacteriophage T5. III. Inhibition of uracil-DNA glycosylase activity. - Warner, H R (1980)
The activity of uracil-DNA glycosylase in Escherichia coli decreases dramatically to less than 10% of its original level after infection of the cells by phage T5. Phage-induced protein synthesis is required for this inhibition to occur, and the inhibition is induced by a mutant capable of injecting only the first 8% of its DNA. The inhibitor activity in extracts of infected cells is heat labile and nondialyzable, and will inhibit enzyme activity present in extracts of uninfected cells.